Magmatic and tectonic fabrics in the La Hoya Pluton, North Patagonian Batholith (43°S) as a record of the early stages of the Andean deformation - Zaffarana, Claudia Beatriz (2020)
Fil: Zaffarana, Claudia. Universidad Nacional de Río Negro. Instituto de Investigación en Paleobiología y Geología. Río Negro, Argentina.